Psychology Software Tool (PST) For Specific Language Impairment Person - et.al, Y.H. Ch’ng (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Specific Language Impairment (SLI) is a disorder categorized by the inability of an individual to master spoken and written language, despite the absence of any apparent handicapping conditions. Many tools have been developed to diagnose or treat SLI, but these tools are largely made up of standalone components which must be utilized separately to obtain sufficient data for the diagnosis and treatment of SLI. Furthermore, some of these components are either very expensive or not widely available. As a result, therapists have faced many inconveniences when trying to treat individuals suffering from SLI. Hence, the development of an integrated, cost-effective Psychology Software Tool (PST) to diagnose and treat SLI is being developed as a solution to counter the inconveniences currently faced by SLI therapists. As a tool by SLI therapists to diagnose and treat SLI within children, the Psychology Software Tool offers standardized questionnaires with a special method to diagnose SLI will be presented in both text and audio, while a webcam will be used to deduce the amount of focus which is given by the patient to comprehend a particular element displayed on the screen. The diagnosis shall take into account the accuracy of answers provided within the questionnaires, the time taken to provide those answers and the aforementioned degree of focus. In terms of SLI treatment, the tool will also provide music therapy for SLI patients to work towards better speech production and comprehension. In short, PST will simplify and enhance the process of diagnosing and treating SLI patients.